As instituiç\~oes de desenvolvimento regional em Portugal, Espanha, Itália e França: Aproximaç\~oes e distanciamentos - Luciléia Aparecida Colombo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The present work aims to present how the regional development has been processed by several institutions, in different countries. In this sense, we will analyze the main regional institutions in countries such as Portugal, Spain, Italy and France, from the analysis of a relevant bibliography, from primary and secondary sources. The preliminary results of this study indicate that the accession of these countries to the European Union was decisive for the national regional policies to be substantively modified.
Keywords: F52; F53; H56; O3; 330; regional development; institutions; public policy